Supplemental copper for growing-finishing swine - Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred forty-four pigs averaging 61 pounds were used to determine the influence of copper level on performance, copper storage in the liver, and to determine the influence of withdrawing during the finishing phase. Pigs fed 125, 187, or 250 ppm copper gained significantly faster (P<.05) than those on the basal diet containing no copper. Responses to copper and to an antibiotic were similar. Most of the growth response from the added copper occurred during the first 8 weeks of the experiment. Withdrawing copper the latter part of the finishing phase influenced neither gain nor efficiency of feed conversion but significantly (P<.05) reduced copper stored in the liver.
Swine Industry Day 1972 is known as Swine Day 1972
Keywords: Swine; Copper; Growing-finishing pigs; Performance